2016
DOI: 10.1128/jvi.01672-16
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus 1 Tegument Protein UL41 Counteracts IFIT3 Antiviral Innate Immunity

Abstract: The interferon-induced protein with tetratricopeptide repeat 3 (IFIT3 or ISG60) is a host-intrinsic antiviral factor that restricts many instances of DNA and RNA virus replication. Herpes simplex virus 1 (HSV-1), a DNA virus bearing a large genome, can encode many viral proteins to counteract the host immune responses. However, whether IFIT3 plays a role upon HSV-1 infection is little known. In this study, we show for the first time that HSV-1 tegument protein UL41, a viral endoribonuclease, plays an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 54 publications
0
42
0
Order By: Relevance
“…In this study, we found that UL41 targeted and reduced cGAS expression by degrading its mRNA. In addition, we and other researchers have demonstrated that UL41 is also involved in HSV-1-mediated immune evasion by targeting several IFN-stimulated genes (ISGs) (17,20,21). Therefore, UL41 is a broad innate immune inhibitor and can block cGAS/STING-mediated IFN signaling at multiple steps.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found that UL41 targeted and reduced cGAS expression by degrading its mRNA. In addition, we and other researchers have demonstrated that UL41 is also involved in HSV-1-mediated immune evasion by targeting several IFN-stimulated genes (ISGs) (17,20,21). Therefore, UL41 is a broad innate immune inhibitor and can block cGAS/STING-mediated IFN signaling at multiple steps.…”
Section: Discussionmentioning
confidence: 99%
“…All enzymes used for cloning procedures were purchased from Vazyme (Nanjing, China). Small hairpin RNA specific for cGAS (shcGAS) and scrambled small hairpin RNA as a negative control (shNC) were cloned into pSUPER.retro.puro vector (Oligoengine, LA) to yield pSUPERshcGAS and pSUPER-shNC plasmids, respectively, as described in our previous study (21). Commercial reporter plasmid pRL-TK (RL stands for Renilla luciferase, and TK stands for thymidine kinase) was purchased from Promega Corporation (Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…lacking UL41 expression was impaired in the presence of ZAP (Su et al, 2015). Similarly, IFIT3 was reported to have no effect on HSV-1 infection (Jiang et al, 2016). As for ZAP, human IFIT proteins with the family members IFIT1, IFIT2, and IFIT3 belong to the subgroup of non-canonical ISGs (Schoggins et al, 2014).…”
Section: Degrading Isg Mrna: Ul41 Counteracts Zap and Ifit3mentioning
confidence: 99%
“…Notably, IFIT3 inhibits the replication of HSV-1 lacking UL41 expression, underlining the importance of UL41 in evading the antiviral effect of IFIT3. The authors showed that UL41 degrades IFIT3 mRNA, but not that of IFIT1 or IFIT2 (Jiang et al, 2016), indicating that HSV-1 may specifically target IFIT3 to prevent the MAVS-TBK1 association, thus suppressing downstream signalling.…”
Section: Degrading Isg Mrna: Ul41 Counteracts Zap and Ifit3mentioning
confidence: 99%